DEVELOPMENT OF NUMERATION LITERACY MODULE BASED ON REALISTIC APPROACH FOR ELEMENTARY SCHOOL - Maya Alemina Ketaren; Dian Armanto; Naeklan Simbolon (FIP Unimed, 2022)
This research aims to expand module study literacy numeration based on approach realistic. Supported from the PISA survey, TIMSS test, and based on the results assessment national student ability in literacy numeration under competence minimum. Type this research is research and development using the ADDIE model. subject in this research students classes IV SDN 104223 Bingkawan. Research results show module study literacy numeration based on realistic approach from the results validation of expert material, expert design and expert language show this module is “Very Eligible” for participants to use in learning education.